Peran Layanan Disabilitas Dalam Meningkatkan Aksesibilitas Informasi Di Perpustakaan Nasional Republik Indonesia - Rahmady, Fachri; Timoria Samosir, Fransiska; Sadiyah, Lailatus (Tik Ilmeu : Jurnal Ilmu Perpustakaan dan Informasi, 2025)
This study aims to analyze the role of disability services in enhancing information accessibility at the National Library of Indonesia (PNRI). Using a descriptive qualitative approach, data were collected through observation, interviews, and documentation. The findings reveal that PNRI provides specialized facilities such as Braille collections, audiobooks, screen readers, dedicated reading rooms, and computers equipped with text to-speech technology to support users with disabilities. However, these services have not fully adhered to the standards set by the IFLA Checklist. Key challenges include limitations in physical infrastructure, funding, adaptive technologies, and librarians' competencies in offering inclusive and disability-friendly services. The study also highlights that the majority of service usage is concentrated among visually impaired users, with less engagement from other disability groups such as hearing-impaired or physically disabled users. Recommendations include enhancing librarians' skills through continuous training, improving physical and technological infrastructure, and fostering strategic collaborations with disability communities and organizations. A more systematic and inclusive approach is expected to improve service quality and broaden accessibility, stablishing PNRI as a truly inclusive information institution.